THE INFLUENCE OF THE PHYSICAL CULTURE AND WELLNESS PROGRAM ON THE HEALTH OF STUDENTS OF SPECIAL MEDICAL GROUPS - Doeva, A.N.; Gagieva, Z.A.; Tskhovrebova, A.I.; Doev, V.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the impact of a sports and recreation program on the restoration of the health status of students of special medical groups. Methods and structure of the study. The experiment was conducted at the Department of General Hygiene and Physical Culture of the Federal State Budgetary Institution of Higher Professional Education «North Ossetia State Medical Academy» of the Ministry of Healthcare of the Russian Federation (FSBI HPE «NOSMA» MOH Russia) from September 2020 to December 2021. We studied 40 students with heart failure, including 20 boys and 20 girls aged 18-19 years. The duration of the disease in most students is two to three years. During the study, treatment was carried out using individual physical education programs to normalize the condition of students. Results and conclusions. At the end of the first year of research on the use of special individual physical exercises for this disease, a positive effect was obtained in restoring the health and working capacity of students of special medical groups. The means of physical education in special medical groups are dosed physical exercises, as well as natural factors of nature and a rational, hygienically justified regimen that provides a healing effect on the body, excluding the formation of bad habits. The main means are therapeutic physical exercises (TPE). A feature of the classes in special medical groups was a large number of exercises that specifically affect individual weakened body systems. It is recommended to conduct sparing mixed-type exercises, since the variety of means used and their modern alternation increase interest in them, give them an emotional coloring and prevent the appearance of fatigue.